An action research on improving the credit initiation process at XYZ Bank - Ang, Mary Geraldine S. (Animo Repository, 2016)
The action research aimed to address the excessive delays in the credit initiation process at XYZ Bank particularly in Makati Business Center (MBC). Using Goldratt's Theory of Constraints (TOC), it was identified that credit initiation is the weakest link that is hindering MBC from maximizing its performance as it takes up 79% of the overall loan process. The issue was affecting the productivity of MBC employees, which translated to lower loan volumes and ultimately, the decrease in interest income of XYZ Bank. By employing root cause analysis and interviews with the branch managers, it was determined that the root cause of the issue stemmed from the unfamiliarity and inadequate knowledge of the branch managers on the basic loan process and documentary requirements. Following TOC's principles, MBC and the branch managers collaborated to focus all efforts in addressing the delays in credit initiation. The joint constructing of the issue and planning of the action led to the agreed upon intervention of conducting training to the branch managers on the basic loan process and documentary requirements. After enacting 2 action research cycles, there was a marked improvement in the turnaround time of applications in the credit initiation stage. However, besides addressing an operational problem, the action research was also able to improve relationships among MBC employees and branch managers who traditionally do not see eye-to-eye when it came to the loan process. The improvement in the relationship of MBC employees and branch managers served as a significant platform to enact the necessary change in the organization. The action research also established that people remain as the critical factor in process improvement as they are the ones accomplishing the tasks embedded in the process thus, companies must continuously equip employees with the necessary knowledge and skills for them to effectively carry out their jobs and enhance their performance. Finally, since process improvement entails change, the action research also stressed the importance of managing organizational politics and fostering meaningful relationships in order to implement change and suggested steps in enacting change in hierarchical organizations like banks following Lewins change model, learning from the action research project and the various theories cited in Coghlan & Brannick (2010)